Surgical safety checklist implementation and its impact on patient safety - Dinesh, H. N.; R. S., Ravya; V., Sunil Kumar (International Surgery Journal, 2018)
Background: Surgery has become an integral part of global health care, with an estimated 234 million operations performed yearly. Surgical complications are common and often preventable. Although surgical and anesthetic caregivers seek to deliver optimal quality in peri-operative service, surgery still carries considerable risk for the patient. WHO surgical safety checklist outlines essential standards of surgical care and has been shown to reduce complications and death associated with surgery. Methods: Pre-intervention and post-intervention study. The effect on patient outcomes and documentation of WHO surgical safety checklist was examined. After an education programme, the checklist implementation and patient safety outcome indicators were studied. Results: Checklist compliance increased over time. The median number of items documented was 16. After implementation of the checklist, mortality decreased from 3.13% to 2.85%. Most causes of death did not significantly differ between the implementation periods, except for multiorgan failure and major bleeding. Adjustment of the association between implementation period and outcome for all variables revealed a decreased mortality after checklist implementation. Conclusions: Implementation of the checklist showed improved outcomes. Use of the WHO surgical safety checklist in urgent operations is feasible and should be considered. Implementation proved neither costly nor lengthy. Further research is needed to confirm these findings and reveal additional factors supportive of checklist implementation.